Application of a drop breakage model using the full energy spectrum and a specific realisation of turbulence anisotropy. (12th October 2021) - Bagkeris, Ioannis; Michael, Vipin; Prosser, Robert; Kowalski, Adam
Highlights: An anisotropic drop breakage model is used in CFD-PBM simulations. Validation is carried out via the exponent of drop size correlations. Experiments report magnitudes of exponent smaller than those predicted by theory. The anisotropic model captures the reduced magnitude of the exponent. The role of the tuning constant c1, b in rescaling breakage velocity is discussed. Abstract: An anisotropic drop breakage model is applied to CFD–PBM simulations of turbulent emulsification in a high–pressure homogeniser. We compare the exponent of Sauter mean diameter – pressure drop correlations with published experimental results and with exponents obtained using existing drop breakage models. Its theoretical value assuming homogeneous isotropic turbulence is - 0.6, while experiments have shown exponents of smaller magnitude. A breakage frequency model using the full spectrum of isotropic turbulence is found to produce a value of the exponent near - 0.6 . Our newly developed anisotropic breakage model predicts an exponent of smaller magnitude, closer to experiments. Breakage frequency based on isotropic turbulence exhibits non–monotonic behaviour (by predicting a maximum value for a certain drop size); the effect of turbulence anisotropy is to reduce non–monotonicity. It is shown that this reduction in non–monotonicity drives the decrease in the magnitude of the exponent.